Transformation of High School or Vocational School Teacher Competencies in the Era of Society 5.0 - Syahlan Mattiro; Mastur; Hamsi Mansur; Bunyamin Maftuh; Encep Syarief Nurdin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
The era of Society 5.0 requires education systems to integrate digital technology and artificial intelligence (AI), positioning teachers as key actors in adaptive and innovative learning. This study aims to describe the performance and competencies of senior high school and vocational school teachers in South Kalimantan Province. A descriptive quantitative design was employed involving 279 teachers and 2,280 students from 30 purposively selected schools representing diverse geographical areas. The main variables measured include teachers’ competence in (1) planning learning (formulating objectives, developing teaching materials, selecting methods and media), (2) implementing learning, (3) evaluating learning outcomes, and (4) utilizing ICT-based learning media. Data were collected using structured questionnaires, observations, and documentation, and analyzed through descriptive statistics (percentage, frequency distribution, mean, median, and mode). The findings show that teacher competence is generally in the “adequate” category. Specifically, 39.4% of teachers are categorized as adequate in formulating learning objectives, 38.4% in selecting learning methods and strategies, and 41.2% in aligning methods with students’ cognitive, affective, and psychomotor development. These results indicate that although teachers have met basic competency standards, their ability to integrate digital technology into pedagogy remains suboptimal. Therefore, systematic and continuous efforts such as applied ICT-based training, mentoring, and strategic collaboration with universities and industry are essential to strengthen teachers’ pedagogical and technological competencies in supporting sustainable educational transformation.